Corrosion behavior of 2205 duplex stainless steel in acidizing stimulation solution for oil and gas wells at 200°C. Issue 2 (11th January 2022) - Du, Juan; Yu, Mengyao; Liu, Pingli; Fu, Yongqiang; Xiong, Gang; Liu, Jinming; Chen, Xiang
Abstract : Purpose: This paper aims to analyze the high temperature (200°C) corrosion behavior of 2205 duplex stainless steel in acidizing stimulation solution containing hydrochloric acid (HCl) and acetic acid. Design/methodology/approach: The corrosion rate of 2205 duplex stainless steel in all kinds of acid solutions was calculated through immersion tests and electrochemical test. The corrosion product composition is analyzed by X-ray diffraction analysis. The element composition and element distribution before and after corrosion were analyzed by an X-ray energy spectrometer. The corrosion morphology of the steel surface was observed by a scanning electron microscope. Both static and dynamic corrosion experiments were carried out at 200°C. Findings: The results show that 2205 duplex stainless steel has excellent corrosion resistance in low to high concentration acetic acid solutions, but increasing the concentration of Cl − in acetic acid solution will accelerate the corrosion rate. Low concentration HCl solution can cause serious corrosion to 2205 duplex stainless steel. The system of HCl and acetic acid will produce a synergistic effect on corrosion of 2205 duplex stainless steel and accelerate the corrosion. Sb2 O3 is a good corrosion inhibitor synergist for high-temperature acidizing stimulation solution. Originality/value: The amount of HCl that is used in acidizing stimulation is usually determined by the dissolution effect of the acid on the rocks, but for ultra-high-temperature reservoirs, the amount of HCl should be based on reducing the corrosion of oil and gas wells.